A Disulfide Bond Is Required for the Transmission of Forces through SUN-KASH Complexes - Jahed, Zeinab (Biophys J, 2015)
Numerous biological functions of a cell, including polarization, differentiation, division, and migration, rely on its ability to endure mechanical forces generated by the cytoskeleton on the nucleus. Coupling of the cytoskeleton and nucleoskeleton is ultimately mediated by LINC complexes that are formed via a strong interaction between SUN- and KASH-domain-containing proteins in the nuclear envelope. These complexes are mechanosensitive and essential for the transmission of forces between the cytoskeleton and nucleoskeleton, and the progression of cellular mechanotransduction. Herein, using molecular dynamics, we examine the effect of tension on the human SUN2-KASH2 complex and show that it is remarkably stable under physiologically relevant tensile forces and large strains. However, a covalent disulfide bond between two highly conserved cysteine residues of SUN2 and KASH2 is crucial for the stability of this interaction and the transmission of forces through the complex.